Effects of Dietary Fish Meal Replaced by Fish Steak Meal on Growth Performance, Antioxidant Capacity, Intestinal Health and Microflora, Inflammatory Response, and Protein Metabolism of Large Yellow Croaker Larimichthys crocea - Dianguang Zhang; Yunzong Zheng; Xuexi Wang; Dejuan Wang; Hongjie Luo; Wenbo Zhu; Weini Zhang; Zhengbang Chen; Jianchun Shao (Aquaculture Nutrition)
Although fish steak meal (FSM) is a potentially available protein source, its efficiency as a fish meal (FM) substitute remains unclear to date. To this end, this study was carried out to determine the effects of dietary FM replaced by FSM on growth performance, antioxidant capacity, intestinal health and microflora, inflammatory response, and protein metabolism of large yellow croaker. Five isolipidic and isonitrogenous diets were formulated by substituting FM with FSM at levels of 0% (FSM0, control diet), 25% (FSM25), 50% (FSM50), 75% (FSM75), and 100% (FSM100), and were fed to juvenile large yellow croaker for 8 weeks. Compared with the control diet, the replacement of 25% dietary FM with FSM did not markedly alter the weight gain (WG) and specific growth rate (SGR). When the FM substitution level was over 25%, WG and SGR markedly reduced. The intestinal structure observation found that the FSM75 and FSM100 diets markedly decreased villus height, villus width, and muscle thickness of the anterior intestine. The FSM75 and FSM100 diets significantly decreased enzyme activities of amylase (AMS), lipase (LPS), trypsin, catalase (CAT), and total superoxide dismutase (T-SOD) and the total antioxidant capacity (T-AOC), and increased the malondialdehyde (MDA) content in the liver of large yellow croaker. The mRNA expression levels of intestinal barrier and inflammatory response-related genes suggested that the FSM50, FSM75, and FSM100 diets significantly decreased the mRNA abundances of intestinal barrier-related genes and anti-inflammatory response-related genes, and increased the mRNA abundances of proinflammatory gene il-6 in the anterior intestine. The compositions of intestinal microflora displayed that the FSM50, FSM75, and FSM100 diets decreased relative abundances of Firmicutes phylum and increased relative abundances of Proteobacteria phylum. In addition, the results of protein expression levels showed that the phosphorylation level of mammalian target of rapamycin (mTOR) and 4E-binding protein 1 (4E-BP1) in FSM75 and FSM100 groups were markedly reduced. In conclusion, FSM can replace up to 25% dietary FM without compromising the growth performance, intestinal health, and protein metabolism of the large yellow croaker.